The Mind of an Engineer - Ghosh, Purnendu; Raj, Baldev (Springer Nature Singapore : Imprint: Springer, 2016)
The Indian National Academy of Engineering (INAE) promotes the endeavour of the practitioners of engineering and technology and related sciences to solve the problems of national importance. The book is an initiative of the INAE and a reflection of the experiences of some of the Fellows of the INAE in the fields of science, technology and engineering. The book is about the reminiscences, eureka moments, inspirations, challenges and opportunities in the journey the professionals took toward self-realisation and the goals they achieved. The book contains 58 articles on diverse topics that truly reflects the way the meaningful mind of an engineer works. .